Thermal conductivity enhancement of compact heat sinks using cellular metals - Fiedler, Thomas (Trans Tech Publications Ltd, 2008)
In this paper, the increase of the effective thermal conductivity of paraffin based heat sinks is investigated by making use of cellular metallic matrixes with open cells which are introduced in the thermal low conductive paraffin wax. Lattice Monte Carlo analyses are conducted on different model geometries of such composites composed of a cellular matrixes and paraffin wax. The dependence of the effective thermal conductivity on the cell geometry and the metal foam matrix material is analysed. Furthermore, a diamond coating is simulated in order to estimate its influence on the effective thermal conductivity.